2016
DOI: 10.1007/s11948-016-9814-x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Student’s Ethical Awareness and Behavior: A New Motivational Model

Abstract: Professional communities are experiencing scandals involving unethical and illegal practices daily. Yet it should not take a national major structure failure to highlight the importance of ethical awareness and behavior, or the need for the development and practice of ethical behavior in engineering students. Development of ethical behavior skills in future engineers is a key competency for engineering schools as ethical behavior is a part of the professional identity and practice of engineers. While engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 42 publications
2
73
0
1
Order By: Relevance
“…Concerning ethics, the study identified the stated importance of both ethics training and ethical behavior within the legal profession, but according to Bairaktarova & Woodcock (2017), the teaching of professional ethics, or motivating students to take professional ethics seriously is not easy. I think the consultant must be the one who is responsible for their advice.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning ethics, the study identified the stated importance of both ethics training and ethical behavior within the legal profession, but according to Bairaktarova & Woodcock (2017), the teaching of professional ethics, or motivating students to take professional ethics seriously is not easy. I think the consultant must be the one who is responsible for their advice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, May and Luth focus on skills like perspective-taking, moral efficacy, moral courage, and moral meaningfulness [25]. Others use Azjen's theory of planned behavior [26] to identify pressures that may influence students' ability to act on their morals [27,28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In our opinion, it is impossible to promote the optimal development of the educational expanse at a university without students' initiative and responsible personal participation. Such participation means that students are aware of their personal roles in this process, and capable of being the author and master of their life path (Bairaktarova & Woodcock, 2017;Clark, Gill, Prowse & Rush, 2017). However, it is not yet known to what extent the value orientations of university students, reflecting personal significance for various types of permissible activity, correspond to this concept.…”
Section: Problem Statementmentioning
confidence: 99%